كفاءات معلمي اللغة العربية في إندونيسيا في القرن الحادي والعشرين - Cahya Setyawan; Akhsan Akhsan (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2020)
In the 21st century is a disruptive era, millennial era, digital age. Information technology and science develop. This development was followed by the development of the human generation, namely generazi Z. This generation is technology literate, multitalent, and creative. In the world of education of course this makes a very extraordinary impact. Arabic language teachers as one of the components of education must follow the flow of globalization. Arabic teachers face many challenges in this era. Therefore there is a standard for Arabic teacher competencies. In the standardization, of course there are efforts made by the government, agencies, institutions and individual teachers in developing and training their competencies. Therefore this paper is a literary paper that discusses how the challenges faced by Arabic language teachers in the 21st century, then the competency standards of 21st century Arabic language teacher as well as the efforts made to develop them.